2023
DOI: 10.3389/fbioe.2023.1235161
|View full text |Cite
|
Sign up to set email alerts
|

A novel 3D biofabrication strategy to improve cell proliferation and differentiation of human Wharton’s jelly mesenchymal stromal cells for cell therapy and tissue engineering

Cristina Blanco-Elices,
Roke Iñaki Oruezabal,
David Sánchez-Porras
et al.

Abstract: Purpose: Obtaining sufficient numbers of cells in a short time is a major goal of cell culturing in cell therapy and tissue engineering. However, current bidimensional (2D) culture methods are associated to several limitations, including low efficiency and the loss of key cell differentiation markers on cultured cells.Methods: In the present work, we have designed a novel biofabrication method based on a three-dimensional (3D) culture system (FIBRIAGAR-3D). Human Wharton’s jelly mesenchymal stromal cells (HWJS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
1
0
0
Order By: Relevance
“…Analysis of the potential cytotoxic effects of Cryo-NFAH on human cells revealed the striking result that cell growth with the Cryo-NFAH leachate was considerably higher than with other commercially available hemostatic leachates, with lower apoptotic and necrotic rates. It has been previously reported [28], [29] that brin has a favorable effect on cell proliferation, likely through the release of growth factors contained in the brin clot [30]. Additionally, our hemocompatibility study revealed no hemolytic effect of Cryo-NFAH.…”
Section: Discussionsupporting
confidence: 64%
“…Analysis of the potential cytotoxic effects of Cryo-NFAH on human cells revealed the striking result that cell growth with the Cryo-NFAH leachate was considerably higher than with other commercially available hemostatic leachates, with lower apoptotic and necrotic rates. It has been previously reported [28], [29] that brin has a favorable effect on cell proliferation, likely through the release of growth factors contained in the brin clot [30]. Additionally, our hemocompatibility study revealed no hemolytic effect of Cryo-NFAH.…”
Section: Discussionsupporting
confidence: 64%